Disruption of classical eyelid conditioning after cerebellar lesions: damage to a memory trace system or a simple performance deficit? - Steinmetz, JE (J Neurosci, 1992)
Over the past 10 years, a number of laboratories have reported that classically conditioned skeletal muscle responses, such as conditioned nictitating membrane/eyelid responses, are critically dependent on activity in the cerebellum. For example, unilateral lesions of the cerebellar interpositus nucleus have been shown to prevent acquisition and abolish retention of the conditioned eyelid response on the side ipsilateral to the lesions without affecting conditioned responding (CR) on the contralateral side. Also, recording studies involving the interpositus nucleus have consistently revealed patterns of neuronal discharge that predict execution of the CR. The lesion and recording studies have generally been cited as evidence that plasticity in the cerebellum is critically involved in the learning and memory of classically conditioned responses. This interpretation was recently challenged by Welsh and Harvey (1989a), who claimed that cerebellar lesions simply produced a performance deficit and speculated that the role of the cerebellum was not in learning and memory processes associated with the CR but only in performance of the eye blink response. Presented here are three experiments that provide additional strong evidence for a critical role of the cerebellum in the learning and memory of the Pavlovian CR. These experiments include (1) demonstrations of complete and permanent CR abolition after appropriate interpositus lesions, (2) a failure to find systematic or persisting decrements in the unconditioned response amplitude (i.e., the eye blink reflex) after appropriate interpositus lesion, and (3) observations of differential effects on the CR and unconditioned response after lesions were placed in populations of motoneurons responsible for executing the eye blink response. These data are discussed in the context of performance versus learning issues; evidence presented here rules out the possibility that interpositus lesion abolition of the eye blink CR is simply due to lesion effects on performance.